NEW APPROACHES TO INCREASING THE CREATIVE ACTIVITY OF YOUTH (Archive of Conferences, 2021)
The article scientifically analyzes the main problems and new approaches to increasing the creative activity of young people. The criteria for creativity are: fluency, characterized by the amount of ideas generated per unit of time; originality - the ability to generate “unique” ideas; susceptibility - sensitivity to unusual details and contradictions; metaphorism - the willingness to work in a fantastic, «impossible» context, the tendency to use symbolic, associative means to express thoughts. Creative management decisions are management decisions, a development process that is creative, and results imply positive outcomes for results.